Analisis Teori Kekuasaan dan Politik Organisasi dalam Pesantren Klasik dan Modern di Indonesia - Dikriyah Dikriyah; Abd. Muid N; Suprihatin Suprihatin (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
This study analyses the dynamics of power and organisational politics in Islamic educational institutions, particularly classical and modern Islamic boarding schools in Indonesia, using a literature review approach. Islamic boarding schools, which historically centred on the charismatic authority of the kiai, are now transforming in response to the demands of modernisation, which is driving a shift towards more rational and bureaucratic management. A comparative analysis of ten recent scientific articles reveals significant differences in sources of legitimacy, power structures, decision-making mechanisms, external relations, resource management, and conflict resolution between the two models of Islamic boarding schools. Traditional pesantren rely on the personal authority of the kiai and patron-client relationships, while modern pesantren employ legal-rational structures, managerial expertise, and external connections. These findings indicate an urgent need to develop a grand theory of Islamic education management that can accommodate the broad spectrum between community and bureaucratic models, as well as consider socio-cultural and political influences. This study contributes to the theoretical and practical understanding of pesantren governance, highlighting the importance of integrating Islamic values with organisational efficiency